Aircraft measurements of tracer correlations in the Arctic subvortex region during the Polar Stratospheric Aerosol Experiment (POLSTAR) - Ziereis, H.; Schlager, H.; Fischer, H.; Feigl, C.; Hoor, P.; Marquardt, R.; Wagner, V. (2000)
Total reactive nitrogen (NOy ), ozone (O 3 ), the tracer nitrous oxide (N 2 O), and carbon monoxide (CO) were measured in situ as part of the Polar Stratosphere Aerosol Experiment (POLSTAR 1 and 2). In total, 14 missions were performed in January and February 1997 and 1998 in the Arctic subvortex region, by using the Deutsches Zentrum für Luft- und Raumfahrt research aircraft Falcon. During the two campaigns, no signatures of nitrification events in the lowermost stratosphere, due to sedimentation and evaporation of aerosol particles containing HNO 3 , were found. Compact correlations were observed between NO y and O 3 , between NOy and N 2 O, and between O3 and N2O. Mean NOy /O 3 ratios observed in the lowermost Arctic stratosphere in 1997 and 1998 were 0.0046 and 0.0030, respectively. During POLSTAR 1, NOy-N 2 O and O 3 -N 2 O slopes compare quite well with results of previous measurements in the lowermost stratosphere. However, indications for a nonstratospheric NOy source, possibly aircraft emissions, were found. During POLSTAR 2, inferred NOy-N 2 O and O 3 -N 2 O slopes were significantly lower than those previously observed in this region. This might indicate transport from lower latitudes to the Arctic subvortex region.